Study of the Hydrogen Evolution Reaction Using Ionic Liquid/Cobalt Porphyrin Systems as Electro and Photoelectrocatalysts - Aguirre-Quintana, M; Aguirre-Quintana, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In this work, the design and manufacture of graphite paste (Gr) electrodes is carried out, including N-octylpyridinium hexafluorophosphate (OPyPF6) ionic liquid (IL) as binder and modification with Co-octaethylporphyrin (Co), in order to study the hydrogen evolution reaction (HER) in the absence and presence of light. The system is characterized by XRD and FESEM-EDX (Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy), confirming the presence of all the components of the system in the electrode surface. The studies carried out in this investigation confirm that a photoelectrocatalytic system towards HER is obtained. The system is stable, efficient and easy to prepare. Through cyclic voltammetry and electrochemical impedance spectroscopy, was determined that these electrodes improve their electrochemical and electrical properties upon the addition of OPyPF6. These effects improve even more when the systems are modified with Co porphyrin. It is also observed that when the systems are irradiated at 395 nm, the redox process is favored in energy terms, as well as in its electrical properties. Through gas chromatography, it was determined that the graphite paste electrode in the presence of ionic liquid and porphyrin (Gr/IL/Co) presents a high turnover number (TON) value (6342 and 6827 in presence of light) in comparison to similar systems reported. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.